1986
DOI: 10.1017/s0007485300014747
|View full text |Cite
|
Sign up to set email alerts
|

The eradication of Glossina palpalis palpalis (Robineau-Desvoidy) (Diptera: Glossinidae) using traps, insecticide-impregnated targets and the sterile insect technique in central Nigeria

Abstract: The integrated use of biconical traps, insecticide-impregnated targets and the sterile insect technique was developed for the eradication of Glossina palpalis palpalis (Robineau-Desvoidy) in a 1500-km 2 area of central Nigeria. Six weeks or more of continuous removal trapping, using biconical traps, reduced the target tsetse population by more than 90% but failed to eradicate it. Males sterilized by irradiation from a ^Co source that were then released weekly induced significant sterility in target females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 6 publications
2
28
0
1
Order By: Relevance
“…The use of traps for control of riverine tsetse fly populations is well documented (Gouteux & Lancien 1986;Takken et al 1986). However, the suppression of tsetse flies with entomopathogenic fungi is a fairly new approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of traps for control of riverine tsetse fly populations is well documented (Gouteux & Lancien 1986;Takken et al 1986). However, the suppression of tsetse flies with entomopathogenic fungi is a fairly new approach.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the measures to control riverine tsetse flies include application of pyrethroid based-insecticides or 'pour-on' (Bauer et al 1995;Leak et al 1995), mass trapping (Gouteux & Lancien 1986;Takken et al 1986), chemical insecticide-impregnated traps or targets (Laveissière & Couret 1981Oladunmade et al 1985), and sterile insect technique (SIT) (Politzar & Cuisance 1982;Takken et al 1986;Oladunmade et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Studies in Zimbabwe have shown that Glossina populations can be eradicated by attracting them to a sparse placement of odour-baited targets (Vale et al, 1986(Vale et al, , 1988. Traps and targets without odour-baits have also been used in conjunction with SIT to eradicate tsetse in Nigeria (Takken et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…First the population was reduced by deploying insecticideimpregnated screens and by removal-trapping with traps (Oladunmade et al 1985, Takken et al 1986) that reduced the native fly population by 90-99% over a 6-12 week period. Extending the period of control, using traps and targets, did not achieve eradication.…”
Section: Direct Insecticide Application For Adult Population Suppressionmentioning
confidence: 99%
“…Extending the period of control, using traps and targets, did not achieve eradication. A major concern was the loss of the screens due to theft, flooding and fire (Takken et al 1986). Then the target population was eliminated over the entire 1500-km 2 area by weekly releases of sterile males from the ground (Oladunmade et al 1990).…”
Section: Direct Insecticide Application For Adult Population Suppressionmentioning
confidence: 99%